Photometric redshifts for the next generation of deep radio continuum surveys – II. Gaussian processes and hybrid estimates. Issue 4 (17th April 2018) - Duncan, Kenneth J; Jarvis, Matt J; Brown, Michael J I; Röttgering, Huub J A
Abstract: Building on the first paper in this series (Duncan et al. 2018), we present a study investigating the performance of Gaussian process photometric redshift (photo- z ) estimates for galaxies and active galactic nuclei (AGNs) detected in deep radio continuum surveys. A Gaussian process redshift code is used to produce photo- z estimates targeting specific subsets of both the AGN population – infrared (IR), X-ray, and optically selected AGNs – and the general galaxy population. The new estimates for the AGN population are found to perform significantly better at z  > 1 than the template-based photo- z estimates presented in our previous study. Our new photo- z estimates are then combined with template estimates through hierarchical Bayesian combination to produce a hybrid consensus estimate that outperforms both of the individual methods across all source types. Photo- z estimates for radio sources that are X-ray sources or optical/IR AGNs are significantly improved in comparison to previous template-only estimates – with outlier fractions and robust scatter reduced by up to a factor of ∼4. The ability of our method to combine the strengths of the two input photo- z techniques and the large improvements we observe illustrate its potential for enabling future exploitation of deep radio continuum surveys for both the study of galaxy and black hole coevolution and for cosmological studies.